Biochemical analysis of mutants with changes in the origin-binding domain of simian virus 40 tumor antigen. - Simmons, D T (1993)
The role of the origin-binding domain of simian virus 40 large tumor antigen (T antigen) in the initiation of virus DNA replication was investigated by analyzing the biochemical activities of a series of mutants with single-site substitutions in this region. These activities include origin-specific and nonspecific DNA binding, melting of the imperfect palindromic sequence, untwisting of the AT-rich region, unwinding of origin-containing DNA, helicase activity, and the ability to oligomerize normally in response to ATP. Three classes of T-antigen mutants that are unable to support virus replication in monkey cells are described. Class 1 mutants are unable to bind to the origin of DNA replication but are able to bind to DNA nonspecifically. Class 2 mutants exhibit defective binding to both types of DNA. As expected, mutants in these first two classes are unable to unwind origin DNA. Surprisingly, however, these mutants possess significant levels of melting and untwisting activities, suggesting that these reactions may not be solely dependent on the ability of the protein to recognize origin sequences. Most class 1 mutants oligomerize normally in response to ATP, indicating that their DNA-binding defects are not due to structural alterations but probably to a failure to directly recognize origin sequences. In contrast, class 2 mutants exhibit defective oligomerization. Class 3 mutants bind to origin and nonorigin DNA at near wild-type levels and melt and untwist origin DNA normally but exhibit defective oligomerization and unwinding. These mutants are, however, perfectly able to carry out the helicase reaction, indicating that their unwinding defect is at some step after melting but before a nonspecific helicase is used to separate parental strands during replication. These results therefore suggest that proper oligomerization to correctly position the molecules on the DNA may be more important in initiating unwinding than in bringing about efficient DNA binding, inducing structural changes in the DNA, or carrying out the helicase reaction.